2007
DOI: 10.1177/0883073807302612
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam in Nonconvulsive Status Epilepticus in Childhood: A Case Report

Abstract: The authors report the case of a child with cerebral palsy and refractory epilepsy who developed nonconvulsive status epilepticus without acute medical cause treated successfully with levetiracetam. In accordance with other studies whose authors hypothesized that aggressive treatment may worsen the prognosis in elderly patients with nonconvulsive status epilepticus, the present authors successfully used a more conservative approach to the treatment of nonconvulsive status epilepticus in their patient. This cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…The first case reports of LEV in SE used the oral formulation, most often applied via a nasogastric tube in critically ill patients with SE [Bhatia et al 2008;Trabacca et al 2007;Feleppa et al 2006;Saguer et al 2006;Veldkamp and Swart, 2006;Mehta and Wu, 2005;PastorMilan et al 2005;Zaatreh, 2005]. These studies included 15 patients with varied types of SE (nonconvulsive ¼ 11, convulsive ¼ 2, myoclonic with coma ¼ 1, not otherwise specified ¼ 1) and suggested a good clinical efficacy with suppression of seizures in almost all cases and good tolerability of acutely administered and rapidly loaded oral LEV.…”
Section: Oral Levetiracetammentioning
confidence: 99%
“…The first case reports of LEV in SE used the oral formulation, most often applied via a nasogastric tube in critically ill patients with SE [Bhatia et al 2008;Trabacca et al 2007;Feleppa et al 2006;Saguer et al 2006;Veldkamp and Swart, 2006;Mehta and Wu, 2005;PastorMilan et al 2005;Zaatreh, 2005]. These studies included 15 patients with varied types of SE (nonconvulsive ¼ 11, convulsive ¼ 2, myoclonic with coma ¼ 1, not otherwise specified ¼ 1) and suggested a good clinical efficacy with suppression of seizures in almost all cases and good tolerability of acutely administered and rapidly loaded oral LEV.…”
Section: Oral Levetiracetammentioning
confidence: 99%
“…However, the evidence supporting its use in pediatric SE is confined to case reports and case series. Levetiracetam has been reported to have efficacy in cases of refractory SE [39][40][41] and also in cases of NCSE [39,42,43]. However, in some series, levetiracetam is reported to have poor efficacy for SE [44].…”
Section: Early or Impending Se Second-linementioning
confidence: 99%
“…A majority of studies have shown that levetiracetam has the most benefit for partial seizures but it does have benefit in generalized tonic-clonic seizures, infantile spasms, neonatal seizures, absence seizures, localization related seizures, nonconvulsive status epilepticus and various other epilepsy syndromes. 3,[53][54][55][56][57][58][59] Patients as young as 2 days old have had positive experiences with levetiracetam with few to no adverse effects. Dosages have ranged from 6 mg/kg/day to 314 mg/kg/day and duration was anywhere from 1 week to 3 years.…”
Section: Use In Pediatricsmentioning
confidence: 99%
“…All of the available literature in pediatric patients seems to describe the efficacy and benefit of utilizing levetiracetam in pediatric patients for many seizure types including status epilepticus and NCSE. 53,58,59 All of these SE incidences were case reports which described successful seizure control with levetiracetam.…”
Section: Use In Pediatricsmentioning
confidence: 99%
See 1 more Smart Citation